العقبـات الاقتصادـية التي تواجـــه العمـــل التنموي في العراق ( فترة ما بعد 2003 ) دراسة تحليلية (المجلة العراقية للعلوم الاقتصادية, 2018)
Following the events of 2003, economic development in Iraq witnessed remarkable deterioration in its levels, causing structural imbalances to be wider in scope. These trends were caused mainly by the lack of distinctive and thorough planning by the central authorities , and to the weakness of government surveillance .As a consequence , many problems and difficulties emerged and imposed serious challenges to economic performance as a whole for the foreseeable future , such as the duality of inflation and Unemployment , government corruption , and external debt problems. The ongoing situation will result in maintaining economic dependency , which in its turn will persist to impose an obstacle to development efforts in Iraq